A WEARABLE DEVICE TO DETECT FALL - ROXSHEN, NASRUN GAI (Universiti Malaysia Sarawak (UNIMAS), 2020)
A wearable device to detect fall is a fall detection system that can be wear by users. It is an Internet-Of-Things (IOT) that implement based on Arduino IDE. There are various method that can be use to develop this device such as Vision based method, Kinematic/Motion based method and Acoustic based Method. In this study, it use Kinematic/Motion based method which applied Accelerometer and Gyroscope Sensor as one of the main components to detect fall. Experiments were conducted by recording the values obtained from the Accelerometer and Gyroscope sensors. The readings for each fall were taken five times and then analysed to find the exact threshold of different types of fall. The results of the experiments were determined based on Receiver Operating Characteristic (ROC) method which was used to test fall action such as forward fall, backward fall, side fall and activities of daily life (ADL) such as sitting walking and running.